Water quality modelling and quantitative microbial risk assessment for uMsunduzi River in South Africa. (29th March 2022) - Ngubane, Zesizwe; Bergion, Viktor; Dzwairo, Bloodless; Troell, Karin; Amoah, Isaac Dennis; Stenström, Thor Axel; Sokolova, Ekaterina
Abstract: South African rivers generally receive waste from inadequate wastewater infrastructure, mines, and farming activities, among others. The uMsunduzi River in KwaZulu-Natal, South Africa, is among these recipients with recorded poor to very poor water quality. To identify parts of the uMsunduzi River that are polluted by Cryptosporidium and Escherichia coli ( E. coli ), this study mapped out pollutants emanating from point and non-point sources using the Soil and Water Assessment Tool (SWAT). Streamflow calibration in the upper and lower reaches of the catchment showed good performance with R 2 of 0.64 and 0.58, respectively. SWAT water quality output data were combined with a Quantitative Microbial Risk Assessment (QMRA) to understand the microbial health implications for people using river water for drinking, recreational swimming, and non-competitive canoeing. QMRA results for Cryptosporidium and pathogenic E. coli showed that the probability of infection for most users exceeds the acceptable level for drinking and recreation as outlined in the South African water quality guidelines, and by the World Health Organization (WHO). The results of this study can be used as a baseline to assess the economic and health implications of different management plans, resulting in better-informed, cost-effective, and impactful decision-making. HIGHLIGHTS: SWAT model identified areas of the uMsunduzi River that were polluted by Cryptosporidium and E. coli . SWAT water quality output data were used in QMRA. QMRA investigated the impacts of river water on canoeists, recreational swimmers, and those who drink the water. uMsunduzi River water is not suitable for drinking and recreation according to QMRA results. These results can inform policies and decision-making within the catchment. Graphical Abstract